All-Cause Mortality Risk with Direct Oral Anticoagulants and Warfarin in the Primary Treatment of Venous Thromboembolism - Roetker, Nicholas S.; Lutsey, Pamela L.; Zakai, Neil A.; Alonso, Alvaro; Adam, Terrence J.; MacLehose, Richard F. (Thrombosis and Haemostasis, 2018)
Oral anticoagulants used for the primary treatment of venous thromboembolism (VTE) include warfarin and the more recently introduced direct oral anticoagulants (DOACs), including rivaroxaban, apixaban, dabigatran and edoxaban. Information on the comparative safety of these medications in routine clinical practice is lacking. We identified patients with diagnoses for VTE and prescriptions for oral anticoagulants using claims data from a large U.S. insurance database from 2012 to 2017. Marginal structural logistic models were used to examine associations between type of oral anticoagulant and risk of all-cause mortality. Of 62,431 enrolees in this analysis, 51% were female and the mean age was 61.9 years. Initial oral anticoagulant prescriptions were for warfarin (n = 35,704), rivaroxaban (n = 21,064) and apixaban (n = 5,663). A total of 1,791 deaths occurred within 6 months of the initial oral anticoagulant prescription. Risk of all-cause mortality was not associated with having a prescription for warfarin versus any DOAC or between any head-to-head DOAC comparisons. Also, associations generally did not vary when stratified by VTE type, sex, age, co-morbidities (including renal disease) or anti-platelet medication use. In this observational study, the associations with all-cause mortality comparing DOACs versus warfarin agree with results from previous clinical trials and observational studies, while the associations for head-to-head DOAC comparisons provide new information on the comparative safety of DOACs. Our findings suggest that other criteria such as patient preference, cost, recurrent VTE risk or bleeding risk should be used when determining the choice of anticoagulant for the primary treatment of VTE.
Keywords: deep vein thrombosis; pulmonary embolism; epidemiologic studies; management of disease